An evaluation of the Acsádi and Nemeskéri Complex Method of adult age estimation in a modern South African skeletal sample. (April 2021) - Meyer, A.; van der Merwe, AE; Steyn, M.
Abstract: The Acsádi and Nemeskéri Complex Method is a multifactorial adult age estimation method that makes use of weighting systems. The Complex Method employs the use of four skeletal elements in assessing age, including the degree of endocranial suture closure, age-related changes to the pubic symphyseal surface, and the internal structural changes observable in the proximal humerus and femur. Acsádi and Nemeskéri reported a very optimistic error margin of ±2.5 years when all four skeletal elements were used. Despite these promising results, the Complex Method's effectiveness has been questioned, suggesting that it results in a constant over- and underestimation of age in younger and older groups, respectively. In this study, the Complex Method was tested on a modern South African skeletal sample ( n  = 313) with individuals of known age-at-death. Results from this study to some extent justify the critique levelled against the Complex Method's tendency to over- and underestimate age. Nevertheless, the Complex Method still performed surprisingly well for certain skeletal element combinations. Contrary to Acsádi and Nemeskéri's findings, the use of all four skeletal elements did not provide more accurate age estimates. For the most part, combinations making use of three or two skeletal elements outperformed the use of all four skeletal indicators. Results from this study indicate caution in using a blanket approach when it comes to deciding on the best combination of skeletal elements used in multifactorial methods. It is suggested that the Complex Method may be optimised by making use of sex- and population-specific skeletal element combinations and weighting systems in the future. Highlights: The Complex Method presented with over-and underestimation of age. Method accuracy increased for age estimation in the fourth to sixth decade of life. The use of all four skeletal indicators did not provide superior results. The proximal humerus should be used as a weighting indicator in the absence of the pubic symphysis. Sex- and population-specific element combinations and weighting systems are advised.